How to Interpret Changes inan Athletic PerformanceTest - Hopkins, W. G. (Sportscience, 2005)
When monitoring progression of an athlete with performance or other fitness tests, it is important to take into account the magnitude of the smallest worthwhile change in performance and the uncertainty or noise in the test result. For elite athletes competing in sports as individuals, the smallest worthwhile change in performance is about half the typical variation in an athlete's performance from competition to competition, or ~0.5-1% when expressed as a change in power output, depending on the sport. In team sports, where there is no direct relationship between team and test performance, an appropriate default for the smallest change in test performance is one-fifth of the between-athlete standard deviation (a standardized or Cohen effect size of 0.20). Noise in a test result is best expressed as the typical or standard error of measurement derived from a reliability study. The noise in most performance tests is greater than the smallest worthwhile difference, so assessments of changes in performance can be problematic. An exact but somewhat impractical solution is to present chances that the true change is beneficial, trivial, and harmful. A simpler approach is to apply systematic rules to decide whether the true change is beneficial, trivial, harmful, or unclear. Unrealistically large changes can also be partially discounted when tests are noisy.